A review on in-tube two-phase heat transfer of hydro-fluoro-olefines refrigerants. (16th November 2016) - Righetti, Giulia; Zilio, Claudio; Mancin, Simone; Longo, Giovanni A.
Abstract : Since 2010, hydro-fluoro-olefines have been experimentally studied during both boiling and condensation with the research productions continuously growing. At a glance, most of the data collected regards the two most available fluids, R1234yf and R1234ze(E), which were tested during two-phase flow both inside and outside smooth and microfin tubes or in brazed plate heat exchangers, as well on other different enhanced surfaces. A few data were obtained with noncommercially available hydro-fluoro-olefines, such as R1234ze(Z). In addition, relevant work has been dedicated to study the heat transfer capabilities of hydro-fluoro-carbon/hydro-fluoro-olefine mixtures. This article presents a critical review on the published research articles on in-tube two-phase heat transfer during boiling and condensation of hydro-fluoro-olefine refrigerants. In particular, a large database of experimental measurements was collected, reviewed, discussed, and then compared against common models to identify the most suitable for all the investigated two-phase heat transfer processes.